Atendimento educacional especializado na educação superior: ações do Núcleo de Acessibilidade da UFSM - Pereira, Daiane Flores (2021)
The present study arose with the intention of broadening the reflections about the actions of Special Education in the context of Higher Education. It is considered that, since 2007, the Federal University of Santa Maria (UFSM) has adopted one policy of reserving vacancies for students with disabilities. This action is a recurring part of Resolution 011, of 2007, the Program for Racial and Social Inclusion; thus enabling students with disabilities to enter the context of Higher Education. Faced with this reality, it was necessary to look at the pedagogical practices that have been developed with these students in order to offer permanence, learning, and course completion. From this perspective, this research aims at understanding how the Specialized Educational Assistance (AEE) practices - developed in the context of the Accessibility Nucleus - are articulated with the school path of students with disabilities with the intention of guaranteeing permanence, learning and curricular integration in the Federal University of Santa Maria/RS. For this, the qualitative research method was used. As data production tools, semi-structured interviews were conducted with the coordinator of the Accessibility Center and the teachers of Special Education who act as post-graduation scholarship holders, developing the Specialized Educational Care at the Accessibility Center. The data analysis was based on the content analysis technique proposed by Bardin (2011). Therefore, different authors who contributed in the construction of the analytical production were used, among them: Tardif (2010), Honnef (2013), Capellini (2008) and Maturana (2001). In addition, legal documents were used to guide the process of inclusion in Higher Education. This investigative movement allowed us to get to know the initial formation and professional performance of the teachers of Special Education who work in the Accessibility Center. The data produced indicated that the teachers - participants in the research - are concerned with developing actions that involve individualized attention to the student, the production of guidelines for the coordination and the teachers of the courses, the formation of teachers, assistance, and the adaptation of materials; also constituting actions that contemplate and help all teachers and subjects who work with these students, sharing knowledge that collaborates for the development of inclusive practices - valuing and respecting the uniqueness of students. Therefore, it was concluded that the work developed in the Accessibility Center, in the context of the Specialized Educational Care, contemplated the actions that covered, from attitudinal, communicational accessibility to methodological accessibility, which contribute greatly to the permanence, learning and curricular integration of students with disabilities at UFSM.